Negotiating Privacy In Collective Housing: A Search For Balance In 800 And 1000 Neighbourhood Batna - Benterki, Toua; Alkama, Djamal; Hamouda, Abida (Journal of Architecture and environment of child, 2024)
This study delves into the intricate relationship between privacy and community engagement within a specific collective housing complex: the 800 neighborhood in Batna, Algeria. While collective housing fosters a sense of community, the inherent proximity and shared spaces can raise privacy concerns. Residents may feel their personal space is compromised by noise or limited control over common areas, potentially leading to isolation and reluctance to participate in community activities. This study aims to explore how residents in the 800 and 1000 neighborhood navigate this interplay between privacy and community engagement. We investigate how feelings of security within their dwelling units influence their comfort level with participating in community life offered by the complex. Our research will utilize a quantitative approach, employing a self-administered questionnaire distributed to residents. The questionnaire will be designed to capture resident experiences within the Algerian context Data analysis will involve descriptive statistics to summarize resident characteristics and responses. We will employ a quantitative data such as observation to explore the relationship between feelings of security within the dwelling unit and comfort level with community activities. Depending on the data complexity, additional techniques like regression analysis may be used to gain further insights. Through this investigation, we expect to gain valuable insights into resident perceptions of the privacy-community balance. The analysis may reveal how cultural values and specific design features of the complex influence this balance. We anticipate a correlation between feelings of security within the dwelling unit and a resident’s comfort level with engaging in community activities. Additionally, the study may identify strategies that residents employ to navigate the privacy-community balance within this specific Algerian context.